Place media events and place image communication: The role of festivals and special events from the perspective of media relations. Issue 2 (27th July 2011) - Feng, Bingqi; Dong, Bing; Xu, Taolong; Feng, Ruofei
This article attempts to demonstrate the significant role played by festivals and special events in place image communication from the perspective of media relations through a review of the literature referring to place image and media relations. By developing the term 'place media event', the authors arise a number of issues in place image communication. The authors argue that to win satisfactory uncontrolled media coverage, the importance of inner place image, media relations practitioners, media logic and routine media relations practices should been highlighted. These factors determine the successful transformation of standard events into media events.